The auditing with environmental focus in the public right cuban - Antúnez Sánchez, Alcides (Derecho Público Iberoamericano, 2015)
The juridical regulation of the environmental auditing in the way of state-owned step Cuban, take aim like a step in the advance of the environmental control for the supreme organ of control. For it, a historic analysis is accomplished, theoretician, member of the parliament of development and evolution of the control through the public audit.